OPTIMIZING THE LANGUAGE ABILITY AND SOCIO-EMOTIONAL ABILITY OF CHILDREN AGED 3 - 4 YEARS THROUGH THE DUR SALINDUR GAME - Tri Endang Jatmikowati; Wahju Dyah Laksmi Wardhani (JURNAL INDRIA (Jurnal Ilmiah Pendidikan Prasekolah dan Sekolah Awal), 2019)
The research aimed to describe how traditional games can be used to optimize speaking competence and children’s social emotion. The traditional game used for this research purpose is from Javanese culture named Dur Salidur. The unique characteristic of the game is the existence of conversation among players for communicating reasons for the group choice. The research method used is action research located in PAUD Labschool Yasmin Playgroup. The data testing was done by using Serial Reaction Time (SRT) with two cycles. The research found that Dur Salidur game was able to be a means of the developing child’s social emotional intelligence. Furthermore, in the second cycle, children could accept other people’s opinion, comply with the agreed rules by showing patience, adjust themselves as well as have an action representing the attitude of curiousity. Besides, the children’s language ability shows an increase through the game rules, giving them a chance to the children to communicate interactively and to keep the dialogue runs smoothly.